Prefektura annony w okresie flawijskim. Uwagi wstępne (Tabularium Historiae, 2019)
The praefectus annonae was responsible for the supply of grain to Rome, which is one of maid food products of the population of the Roman Empire. The office praefectus annonae was created by Augustus, the emperors of flavian dynasty filled it regularly. In equestrian cursus honorum this function has really great importance, it was one of the main equestrian offices. The office praefectus annonae is the intermediate post between the function praefectus vigilum and praefectus Aegypti, it could crown the career of equites or be an indirect element of the administrative career.